Assessing ventilatory efficiency at rest in asthma: A longitudinal comparison with healthy subjects - Monique vanOosten; Arni Johnsen; Bjorn Magnusson; Marta Gudjonsdottir (Physiological Reports)
Abstract Dysfunctional breathing, characterized by inefficient ventilation, is common among asthmatic patients. It is mainly identified using questionnaires and by observing breathing patterns, but the actual efficiency of ventilation is rarely evaluated. This study aimed to compare ventilatory efficiency at rest between asthmatic patients and healthy subjects, and to assess the stability of these parameters over 1 year. Ventilation (VE), respiratory rate (RR), tidal volume (VT), carbon dioxide output (VCO2) and end‐tidal partial pressure (PETCO2), spirometry, and breath‐holding time (BHT) were measured at baseline (M1) and 17–51 weeks later (M2). The ventilatory efficiency (VE/VCO2) and breathing pattern (RR/VT) were calculated. Patients took the Asthma Control Test questionnaire (ACT). A mixed‐design ANOVA at M1 showed that 30 not well‐controlled asthmatic patients according to ACT (77% females, 7 with airway obstruction), and 23 matched healthy subjects had similar breathing parameters, except for BHT (p < 0.02) and PETCO2 (p = 0.06). Only BHT changed, that is, it increased from M1 to M2 in the groups and remained shorter among the patients. Despite a shorter BHT among the patients, indicating a heightened perceptual sensitivity for dyspnoea, the ventilatory efficiency and breathing pattern at rest were similar and remained stable for 1 year in both groups.